Responsabilidade social e justiça intergeracional: o caso FEMSA - Ferreira, Cristiano (2009)
This work is based on the assumption that the water sources preservation and the water conservation must be in subjection of the distributive and intergeneration justice. And it is concerned, particularly, to examine how its worry about future generations is shown in official speeches of a company which main production input is the water. Thus, it tries to relate the water, social responsibility and intergenerational justice issues. To accomplish it, John Rawls’ notion of intergenerational justice was chosen as an analytical parameter. This research is highly qualitative and the chosen methodology is document and content analysis. In short, we can conclude that the chosen company presents in its documents a highlighted concern with environment preservation where the well-being needs of future generations are taken into account.